Thermodynamics of hydrogen bonding and van der Waals interactions of organic solutes in solutions of imidazolium based ionic liquids: “Structure-property” relationships - Varfolomeev, Mikhail A.; Khachatrian, Artashes A.; Akhmadeev, Bulat S.; Solomonov, Boris N. (Thermochimica acta, 2016)
[Display omitted] •Solution enthalpies of organic solutes in imidazolium based ionic liquids were measured.•van der Waals interactions scale of imidazolium based ionic liquids was proposed.•Enthalpies of solvation of organic solutes in ionic liquids were determined.•Hydrogen bond enthalpies of organic solutes with ionic liquids were calculated.•Relationships between structure of ionic liquids and thermochemical data were obtained. In the present work thermochemistry of intermolecular interactions of organic compounds in solutions of imidazolium based ionic liquids (ILs) has been studied using solution calorimetry method. Enthalpies of solution at infinite dilution of non-polar (alkanes, aromatic hydrocarbons) and polar (alcohols, amides, and etc.) organic solutes in two ionic liquids 1-butyl-3-methylimidazolium tetrafluoroborate and 1-butyl-3-methylimidazolium trifluoromethanesulfonate were measured at 298.15K. The scale of van der Waals interactions of imidazolium based ILs has been proposed on the basis of solution enthalpies of n-alkanes in their media. The effect of the cation and anion structure of ILs on the enthalpies of solvation was analyzed. Enthalpies of hydrogen bonding of organic solutes with imidazolium based ILs were determined. It has been shown that these values are close to zero for proton acceptor solutes. At the same time, enthalpies of hydrogen bonding of proton donor solutes with ionic liquids are increased depending the anion: tetrafluoroborate≈bis(trifluoromethylsulfonyl)imide<2-(2-methoxyethoxy)ethyl sulfate<trifluoromethanesulfonate. Enthalpies of van der Waals interactions and hydrogen bonding in the solutions of imidazolium based ionic liquids were compared with the same data for molecular solvents.